Pengantar Ilmu Hukum dan Hubunganya Dengan Keimigrasian dan Undang-Undang Nomor 6 Tahun 2011 Tentang Keimigrasian - Hardyano Fatih Warganegara; Andrianus Bagas Wahyu Putranto; Andhi Nur Saputra (Unram Law Review, 2022)
Human’s life cannot be separated from the law, starting from the actions by individual even group, the way people’s conducting their life, think, and punishment as a result of violation to the act. The purpose of this study is to introduce the basic provisions concerning the definition of Immigration law in Indonesia, the structure of the act and its implementation in the community by virtue of Immigration Act number 6 year 2011. The method of this study using normative legal research. The approach are statutory and conceptual approach. The result shows that the implementation of Migration Policy in Indonesia depends on the legal truth which is acceptable in the community such as customs which still considers binding in the society whether in the form of policy, principles, sanctions, etc.